A escrita de alunos do ensino fundamental: alguns aspectos formais e discursivos - Silva, Orley José (2012)
This dissertation aims to analyze and to explain some aspects of discourse found in pairs of texts written by students of two classes of the last phase of Cycle III of the Elementary School, from a public school in the city of Goiania. We also want to understand how students critically position themselves in the face of discursive voices proposals; to investigate what discursive formations are most employed in the construction of the text, and promote reflections that can contribute to improve the teaching of text production in the classroom. From all the collected writing activities, we made a selection of 15 pairs of texts produced by 15 students. Each pair consists of two versions prepared by the same student. This research underlies on the theory of dialogism and enunciation, according to Bakhtin (1997, 2003) and other scholars who took the writing process, the discourse and the text as the focus of their inquiries, such as: Authier-Revuz (1990), Foucault (2005), Koch (2006), Orlandi (2005, 2006), Pêcheux (1990, 1997, 1999). It is characterized as a participant observation research that, besides presenting interpretative features, allows the interaction between the researcher and the group to be researched. The rationale of our investigation is linked to the necessity of better understanding the process of writing production in the classroom. Our analysis provides opportunities to confirm that the students are able to cope with the heterogeneity of voices in society and to appropriate them in their discourses; to establish cohesion and coherence in their enunciation produced at different times; to use argumentative strategies in order to convince the reader; to give continuity to the same theme in subsequent lessons. Finally, we noticed that the teacher can work the same theme in different classes without running the risk of becoming repetitive.